Cultura: Un enfoque desde lo imaginario - Herrera Guido, María Teresa Catalina (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
We have trafficked to a new millennium where the human beings you they question on the direction it will follow the mankind in this planet. Those more important paradigms of the Modernity have been between parenthesis and the new paradigms have not been profiled completely. We are immerses in a limit of possibilities among what is and what will be. One of the manifestations of our time is the repetition of certain cultural expressions in the whole terraqueous globe that you/they foreshadow a culture world. This phenomenon becomes patent in the music, urban architecture, gears, use of new technologies, graffiti, economy, to mention some that suggest a supracultura that suffocates the cultural diversity and the subjectivity. From this perspective we wonder: What consequences does he/she have for the cultures you would originate, that world other supracultura? In the constitution of the imaginary thing is presupposed an interpretive activity and an effort of knowledge; the texts of world class don't say enough to the cultures? The imaginary one as concept, it is transformed by this phenomenon? To sketch possible answers to these queries, us we intend to approach three work lines: the first, to elucidate the process of conformation of the imagination, and their relationship with the imaginary thing, for it us we will bring near to the concepts of sensibility, imagination and the imaginary thing properly this; the second, how it is that in the coordinates of the time, space, language, is located in the imaginary thing; and in third o'clock, we approach the one concept of the imaginary thing in the culture, through the diverse and multiple world of the human thing, the modern and postmodern vision of world, as well as the configuration of a world culture starting from the globalization.

Hemos transitado a un nuevo milenio en donde los seres humanos se cuestionan sobre el rumbo qué seguirá el género humano en este planeta. Los paradigmas más importantes de la Modernidad han quedado entre paréntesis y los nuevos paradigmas no se han perfilado del todo. Estamos inmersos en un límite de posibilidades entre lo que es y lo que será. Una de las manifestaciones de nuestro tiempo es la repetición de ciertas expresiones culturales en todo el globo terráqueo, que prefiguran una cultura mundial. Este fenómeno se hace patente en la música, arquitectura urbana, vestimentas, uso de nuevas tecnologías, grafiti, economía, por mencionar algunas, que sugieren una supracultura que sofoca la diversidad cultural y la subjetividad. Desde esta perspectiva nos preguntamos: ¿Qué consecuencias tiene para las culturas originarias, esa otra supracultura mundial? ¿En la constitución de lo imaginario se presupone una actividad interpretativa y un esfuerzo de conocimiento; los textos de clase mundial no dicen lo suficiente a las culturas? ¿El imaginario como concepto, se ve trastocado por este fenómeno? Para esbozar posibles respuestas a estas interrogantes, nos proponemos abordar tres líneas de trabajo: la primera, dilucidar el proceso de conformación de la imaginación, y su relación con lo imaginario, para ello nos acercaremos a los conceptos de sensibilidad, imaginación y lo imaginario propiamente dicho; la segunda, cómo es que en las coordenadas del tiempo, espacio, leguaje, se enclavan en lo imaginario; y en la tercera, abordamos el concepto de lo imaginario en la cultura, a través del mundo diverso y múltiple de lo humano, la visión moderna y posmoderna de mundo, así como la configuración de una cultura mundial a partir de la globalización.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2011-0036; Imaginario; Sensibilidad; Mundo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/66